Las consecuencias demográficas de la austeridad en América Latina : aspectos metodológicos - Hakkert, Ralph (El Colegio de México A.C., 1991)
The demographic impact of the economic crisis of the 1980s in the Third World is analyzed, with a focus on Latin America. The paper emphasizes the methodological problems involved in measuring such impacts. Apart from the ever present difficulties in ob- taining up-to-date information on fertility, mortality, and especially migration in the context of scarce and deficient data sources, the conceptual difficulties inherent in establishing the relationships are discussed. These include the difficulty of differentiating between short term and structural effects, especially in fertility, the presence of time lags and different time frames, the need to differentiate between types of economic swings, and the counteracting effects that may conceal expected interactions, especially in mortality. Migration, perhaps the most sensitive demographic component in this respect, is also the one where the expected direction of the impact is most difficult to establish. The differences between the cross-sectional analyses common in the current demographic literature and the longitudinal view needed in studies of this kind is discussed.